The Rescue of Streetcar 304 : a Navy Pilot's Forty Hours on the Run in Laos. - Fields, Kenny (Naval Institute Press, 2011)
On 31 May 1968, Navy Lt. Kenny Fields catapulted off USS America, in his A-7 Corsair II on his first combat mission. His target was in Laos, which at the time was officially off-limits for U.S. attacks. Fields call sign Streetcar 304 was the first to roll in and destroyed the target with a direct hit. Three AAA guns began to fire, but, following his wingman, he rolled in again. This time many more AAA guns opened up and Fields was shot down hitting the ground with enemy troop in hot pursuit. The Rescue of Streetcar 304 is Fields exhilarating narrative of the 40-hour ordeal that followed, in wh.